Response of lightning NOx emissions and ozone production to climate change: Insights from the Atmospheric Chemistry and Climate Model Intercomparison Project. Issue 10 (31st May 2016) - Finney, D. L.; Doherty, R. M.; Wild, O.; Young, P. J.; Butler, A.
Abstract: Results from an ensemble of models are used to investigate the response of lightning nitrogen oxide emissions to climate change and the consequent impacts on ozone production. Most models generate lightning using a parameterization based on cloud top height. With this approach and a present‐day global emission of 5 TgN, we estimate a linear response with respect to changes in global surface temperature of +0.44 ± 0.05 TgN K −1 . However, two models using alternative approaches give +0.14 and −0.55 TgN K −1 suggesting that the simulated response is highly dependent on lightning parameterization. Lightning NO x is found to have an ozone production efficiency of 6.5 ± 4.7 times that of surface NO x sources. This wide range of efficiencies across models is partly due to the assumed vertical distribution of the lightning source and partly to the treatment of nonmethane volatile organic compound (NMVOC) chemistry. Careful consideration of the vertical distribution of emissions is needed, given its large influence on ozone production. Key Points: Lightning emissions respond linearly to global mean surface temperature change across a range of climate‐chemistry models The response of lightning to climate change is strongly dependent on the lightning parameterization used Ozone production from lightning NO x is 6.5 times more efficient than surface NO x, but there is large variation across models